Benzene-Toluene-Xylene (BTX) Removal from Polluted Airflow by Combined Filter of Zero Valence Iron and Copper oxide Nanoparticles on Iranian Amended Clinoptilolite Bed - Rostami R, Jonidi Jafari A, Rezaei Kalantari R, Gholami M, Esrafili A (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2011)
BACKGROUND AND OBJECTIVE: The BTX compounds consist of benzene, toluene and xylenes are volatile organic compounds and are present in fuels and industrial solvents. Its emission to air and exposure to these compounds threats human health. Thus, it is necessary to control these compounds concentration in acceptable limit. Therefore, the purpose of this research was to survey BTX removal ability of a compound of iron and copper oxide metallic nanoparticles which have catalytic properties and also Zeolite as a sorbent and media for nanoparticles.METHODS: In this experimental study, samples were taken from inlet and outlet airflow of reactor for BTX and CO2 concentration determination. Zeolite filters without nanoparticle and a compound of zeolite with zero valence iron and copper oxide nanoparticles which contains 4.5% of nanoparticles and with 1-2mm of zeolite grains size as much as 200g were prepared and the BTX removal by each filter in a 30cm in length and 4.5 cm in diameter column as reactor determined. FINDINGS: The removal efficiency of benzene in the filter without nanoparticle (78.30±5.37%) was more than Iron and copper oxide nanoparticles (49.64±4.19%). But, for the toluene (67.09±4.23%) and xylenes (39.86±2.04%, 47.59±3.24% and 80.73±5.98%, respectively for p, m and o-xylenes) in iron and copper oxide nanoparticles filter it was further than the filter without nanoparticles (toluene 62.10±3.25% and xylenes respectively 30.20±1.84%, 32.15±3.39% and 18.80±3.39%). Also, the pollutant complete decomposition was higher in the filter containing nanoparticles (82.78% versus 16.44%). Average removal efficiency of BTX in the filter without nanoparticle was 43.31% and in the filter with iron and copper oxide nanoparticles was as much as 56.98%. CONCLUSION: As the obtained results the filter of zeolite without nanoparticle mainly removes the BTX compounds by absorption or incomplete decomposition. While, the zeolite filter with iron and copper oxide nanoparticles performs decomposition of the BTX more completely to CO2.